Kompleksnost proračuna učinka lučkih obalnih prekrcajnih sredstava - Dundović, Čedomir (Promet - Traffic&Transportation, 2012)
The loading efficiency of harbor quayside and mobilecranes affects significantly the time duration a ship has tospend at a quay. Therefore, the dimensions of the quaysideloading equipment have to he detennined precisely on the basis of hypothetical production efficiency or the actual loadingcapacity of the harbor quayside and/or mobile cranes.When determining the theoretical average efficiency it issupposed that all the variable factors are contained within theposition of the starting point of the crane hook path, the positionof a half-loaded ship, mean sea level, and the distance ofthe ship center-line from the end point of the hook path at thequayside.The author studies the possibilities to peiform a more correctevaluation of efficiency of harbor quayside and mobilecranes, using the developed analytical method for calculatingthe time duration of the operating cycle traject01y.The applied method is based on the assumed conditionsand empirically determined factors that define single parametersin the path of the gripping device material point in order tofind out the necesswy simplifications in calculating the efficiencyof harbor loading equipment.